Responses to Wood and Wood Extractives of Neobalanocarpus heimii and Shorea ovalis by the drywood termite, Cryptotermes cynocephalus (Isoptera : Kalotermitidae) - Sajap, Ahmad Said; Sahri, Mohd Hamami (1983)
Drywood termites, Cryptotermes cynocephalus Light, were exposed to wood blocks and wood extractives of Neobalanocarpus heimii King and Shorea ovalis' Korth.} Bl. The results showed that the termites' survival and wood consumption were significantly higher on S. ovaHs than on N. heimii. Termite survival and feeding response obtained on bioassays with sawdust, extracted sawdusts and extract treated filter paper, indicated that one factor affecting the variation in relative susceptibility of the woods to termite attack could be secondary compounds present in the wood.